Ice-nucleating particles active below −24 °C in a Finnish boreal forest and their relationship to bioaerosols - F. Vogel; F. Vogel; M. P. Adams; L. Lacher; P. B. Foster; G. C. E. Porter; G. C. E. Porter; B. Bertozzi; B. Bertozzi; K. Höhler; J. Schneider; T. Schorr; et al. (Atmospheric Chemistry and Physics)
Cloud properties are strongly influenced by ice formation; hence, we need to understand the sources of ice-nucleating particles (INPs) around the globe. Boreal forests are known as sources of bioaerosol, and recent work indicates that these dominate the INP spectra above −24 °C. To quantify the INP population at temperatures below −24 °C, we deployed a portable cloud expansion chamber (PINE) in a Finnish boreal forest from 13 March 2018 to 11 May 2018. Using the 6 min time resolution PINE data, we present several lines of evidence that INPs below −24 °C in this location are also from biological sources: (i) an INP parameterization developed for a pine forest site in Colorado, where many INPs were shown to be biological, produced a good fit to our measurements; a moderate correlation of INPs with aerosol concentration larger than 0.5 µm and the fluorescent bioaerosol concentration; (ii) a negative correlation with relative humidity that may relate to enhanced release of bioaerosol at low humidity from local sources such as the prolific lichen population in boreal forests; and (iii) the absence of correlation with ultra-fine particles (3.5 to 50 nm), indicating that new particle formation events are not sources of INPs. This study should motivate further work to establish whether the commonality in bioaerosol ice-nucleating properties between spring in Finland and summer in Colorado is more generally applicable to different coniferous forest locations and times and also to determine to what extent these bioaerosols are transported to locations where they may affect clouds.